Ø¨ÙŠÙˆØ¹ Ø§Ù„Ø´Ø§Ø¦Ø¹Ø© Ùˆ Ù…Ø¹Ø§Ù…Ù„Ø§Øª Ø§Ù„Ù…Ø§Ù„ÙŠØ© Ø§Ù„Ø±Ø¨ÙˆÙŠØ© ÙÙŠ Ù…Ù†Ø¸ÙˆØ± Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ùˆ Ø§Ù„Ù…ØØ¯Ø«ÙŠÙ† - Desmadi Saharuddin; Nuril Mufidah (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2019)
This study aims to introduce people to sharia law and the basics of the correct Islamic legal method for general sale and purchase transactions and usury-containing transactions. Trade differs from riba, and if there are similarities between the two in practice such as installments, the difference is that Allah has allowed trade because of necessity, and riba is forbidden because it multiplies payments/interest. Interest is to multiple payments/installments determined by the lender/owner of the goods. Like selling one sha 'wheat with one-half sha' after maturity, or borrowing a thousand dirhams and paying a loan of one thousand one hundred dirhams. Whereas halal trade/bai, for example, goods/commodities which are currently worth one thousand and the following month become one thousand one hundred, this is not a riba but a kind of tolerance in sales, because buyers take non-dirham / money commodities and do not multiply borrowed goods. It is important to note that this relates to the essential aspects of contemporary Islamic economic problems and emerging problems, such as online sales, brand sales, counterfeit goods, etc